2021
DOI: 10.1109/access.2021.3133483
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of Fault-Tolerant Circuits in Small-Scale Quantum Processors

Abstract: Experiments conducted on open-access cloud-based IBM Quantum devices are presented for characterizing their fault tolerance using [4, 2, 2]-encoded gate sequences. Up to 100 logical gates are activated in the Ibmq_Bogota and Ibmq_Santiago devices and we found that a [4, 2, 2] code's logical gate set may be deemed fault-tolerant for gate sequences larger than 10 gates. However, certain circuits did not satisfy the fault tolerance criterion. In some cases the encoded-gate sequences show a high error rate that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…It is shown that errors in this protocol cannot be corrected. Following this protocol, fault-tolerant error detection of encoding has been demonstrated in trapped ions 34 , superconducting qubits 35 , and the IBM quantum devices 36 38 . However, the key aspect of the quantum circuit implementing with fault-tolerant operations, that is, the existence of the threshold of error rate below which the circuit is realized in a fault-tolerant manner, has not been explicitly demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that errors in this protocol cannot be corrected. Following this protocol, fault-tolerant error detection of encoding has been demonstrated in trapped ions 34 , superconducting qubits 35 , and the IBM quantum devices 36 38 . However, the key aspect of the quantum circuit implementing with fault-tolerant operations, that is, the existence of the threshold of error rate below which the circuit is realized in a fault-tolerant manner, has not been explicitly demonstrated.…”
Section: Introductionmentioning
confidence: 99%